Meningkatkan Prestasi Dengan Bermain Sambil Berlatih di SDN Kauman 02 Kecamatan Juwana Kabupaten Pati - Ninik Sukarni (Peneliti.net, 2023)
Smoking foodstuffs, especially fish is one of the oldest traditional. Based on preliminary observations that the author made at SDN Kauman 02, Juwana District, Pati Regency, student interest and learning outcomes were very low. The cause of low interest and learning outcomes is a lack of interest in learning because they consider some of the subjects taught by the teacher as difficult and boring learning. In this case an effective learning method is needed. This research aims to improve and enhance the learning process in order to achieve learning objectives. Based on this description, alternative solutions that can be offered are the application of a learning while playing and practicing approach. The advantage of this approach is that it can encourage children's interest and learning outcomes, by playing children usually do not realize that they are learning something, because their main focus is interest in the game. The results of the study show that through playing while practicing, the authors managed to overcome teacher barriers in teaching and learning activities thereby increasing student achievement. Through playing while practicing children can learn to accept, express and overcome problems in a positive way. From playing it also provides opportunities for children to know themselves and develop cognitive satisfaction in life so that achievement increases